Detailed Reaction Mechanism of Bis‐(o‐Aminomethylphenylboronic Acid)‐based Receptors with Various Length Methylene‐chain Linkers with D‐Glucose. Issue 29 (1st August 2022) - Ohno, Yuki; Tanaka, Rei; Suzuki, Yota; Sugaya, Tomoaki; Iwatsuki, Satoshi; Inamo, Masahiko; Ishihara, Koji
Abstract: The detailed reaction mechanisms of several bis‐( o ‐aminomethylphenylboronic acid)‐based receptors, linked with methylene chains of different lengths ( i. e ., DBAn (n=2, 3, and 4) having 2n methylene groups), with D‐glucose were kinetically investigated in methanolic aqueous solutions. The p K a measurements showed that the two boronic acid moieties in DBAn were equivalent and had no electronic interaction between them. DBA2 reacted with D‐glucose to form a 1 : 1 product, in which two boronic acid moieties in one molecule of DBA2 were bound to two reactive sites in one molecule of D‐glucose. DBA3 and DBA4 reacted with D‐glucose to form a 1 : 2 product, in which the two boronic acid moieties in one molecule of DBA3 or DBA4 were bound to two molecules of D‐glucose simultaneously through one reactive site. Thus, in the recognition of D‐glucose, the distance between the two boronic acid moieties in DBAn was optimal for n=2 and too long for n=3 or 4. Abstract : The detailed reaction mechanisms of diboronic acids (DBAn, n=2–4) with D‐glucose were kinetically investigated. The p K a measurements showed that the two boronic acid moieties in DBAn were equivalent and had no electronic interaction between them. DBA2 reacted with D‐glucose to form a 1 : 1 product, whereas DBA3 and DBA4 formed a 1 : 2 product. In D‐glucose recognition, the optimal distance between the two boronic acid moieties in DBAn was for n=2.